Response Suppression of Multiple Hinged Floating Structures by Using Rubber Cushion - Ye Lu; Qijia Shi; Yuchao Chen; Wenhui Zheng; Ye Zhou (Shock and Vibration)
A brand-new rubber cushion is proposed in this paper, which is installed between hinged floating modules in order to reduce the relative motion of the pitch; meanwhile, the cushion can be used as a fender for anti-impact in the docking process. Using the linear wave potential method, the structural dynamic model is formulated where the equivalent stiffness matrix for the rubber cushion is obtained by an integrating method employing linear assumption in addition to considering the heterogeneity of rubber. A numerical analysis is presented for a two-module semisubmersible floating structure. The hydrodynamic responses and connector loads of the floating structures with a rubber cushion are analyzed by using the frequency domain approach in both regular and irregular waves. The topological design and stiffness parameter selection of the rubber cushion is studied. This work may provide a new idea for suppressing the pitch motion of multiple hinged floating structures.